Alcohol intake exacerbates experimental autoimmune prostatitis through activating PI3K/AKT/mTOR pathway-mediated Th1 differentiation - Shun Xu; Shun Xu; Shun Xu; Jing Chen; Jing Chen; Jing Chen; Shaoyu Yue; Shaoyu Yue; Shaoyu Yue; Yifan Zhang; Yifan Zhang; Yifan Zhang; et al. (Frontiers in Immunology)
BackgroundEpidemiological investigations have revealed a significant association between alcohol consumption and chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Nevertheless, the potential mechanisms are still inadequately revealed. This research aimed to investigate the impact of alcohol on CP/CPPS using an animal model and to elucidate the underlying mechanisms.MethodsWe first established the widely used animal model for CP/CPPS, experimental autoimmune prostatitis (EAP). During the induction of EAP, mice were fed with alcohol or control diet. The HE staining, ELISA, and behavioral experiments were employed to assess the severity of inflammation in EAP mice and EAP-alcohol mice. Patients with a history of chronic alcohol consumption were also included to evaluate the effects of chronic alcohol consumption on CP/CPPS. Subsequently, proteomic analysis, flow cytometry, immunofluorescence, Western blotting, and immunohistochemistry were utilized to investigate the underlying mechanism involved both in vivo and in vitro.ResultsHE staining, ELISA, and behavioral experiments showed that alcohol exacerbated the severity of EAP in mice and patients. Proteomic and KEGG pathway analyses showed that abnormal Th1 differentiation and PI3K/AKT/mTOR pathway were significantly enriched. Subsequent mechanistic research showed that alcohol significantly activated PI3K/AKT/mTOR pathway and increased the Th1 cell differentiation both in vivo and in vitro. In contrast, PI3K inhibitor LY294002 and shRNA-PI3K plasmid inhibited PI3K/AKT/mTOR pathway activation, reduced Th1 cell differentiation, and alleviated EAP inflammation severity, respectively.ConclusionOur study is the first to demonstrate that alcohol intake promotes Th1 cell differentiation and exacerbates EAP by activating the PI3K/AKT/mTOR pathway. Additionally, the role of LY294002 in inhibiting PI3K/AKT/mTOR pathway to relieve EAP suggests that it can serve as a promising therapeutic target for CP/CPPS.